The effects of social media influencers and pet attachment on the purchasing behavior of undergraduate RVR-COB student dog and cat owners in De La Salle University - Aguilar, Chelsea Grace Salazar (Animo Repository, 2023)
This research study aims to find out if Social Media Influencers and Pet Attachment have an impact and relationship on the Purchase Behavior of Undergraduate RVR-COB Student Dog and Cat Owners in De La Salle University. Social Media Influencers are deemed as experts and information leaders in their field which allow them to influence the decision-making of the people who follow them (Gaenssle & Budzinski, 2021). Pet Attachment is referred to as the deep bond and connection formed by people with their companion animals (Apaolaza et al., 2022). Purchase Behavior is the process in which consumers make their decision when purchase good and services which can be affected by a numer of factors (Apaolaza et al., 2022). This research is descriptive, causal exploratory, and quantitative and was conducted in De Lasalle University in Manila, with a sample population size of 252. Data was gathered using a 4-point Likert survey questionnaire. The data collected was analyzed using descriptive analytics, linear regression, multiple linear regression and Pearson’s correlation analysis. The methods of testing stated above was utilized to answer the 6 hypotheses the researchers have presented. The results from the tests and analyses ran in this research showed that Social Media Influencers and Pet Attachment both positively and significantly affect Purchase Behavior. Furthermore, the results from the linear and multiple regression tests indicated that both regression models are significant as well. Based on the analyses conducted, Social Media Influencers and Pet Attachment is a significant predictor for Purchase Behavior.